Creating Synergistic Approach to Combat Lifestyle Related Diseases and Improved Quality of Life Through Workplace Physical Activity And Wellness Intervention Program - Jaiyesinmi, Boluwaji (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
In the 1970s, workplace health promotion programmes started to emerge as an adjunct to occupational health and safety initiatives. Workers were encouraged to participate in programmes designed to encourage physical activity, healthy eating, and smoke-free living. The health of the employee is very paramount to an organization as it determines the level of functionality of the employee and his ability to go about his duties. This paper examines the possibility of creating synergistic approach to combat lifestyle related diseases that have crippled several potentials in the workplace and improve quality oflife through workplace physical activity and wellness intervention programme.